Application of MEMS Accelerometer for Detection and Diagnosis of Multiple Faults in the Roller Element Bearings of Three Phase Induction Motor - Maruthi, G. S.; Hegde, Vishwanath (IEEE sensors journal, 2016)
This paper presents a simple, non-electrical contact approach to detect and analyze multiple faults in the roller element bearings of three phase induction motor by vibration analysis using microelectromechanical systems (MEMS) accelerometer. The ability of the proposed method has been investigated experimentally under no load, single phase and unbalanced voltage conditions. The frequency analysis of motor vibration due to bearing fault has been carried out by fast Fourier transform algorithm. The appearance of fault frequencies in vibration spectrum will indicate multiple faults in the bearings and also the existence of side-band frequency components around fundamental frequency component indicates air gap modulation due to bearing fault. Experimentally obtained fault frequencies are compared with analytical values and found that both are closely matching. This indicates that the proposed method can be reliably employed to detect from simple to complex faults in the bearings of induction motor using MEMS accelerometers.